2018
DOI: 10.1590/1980-5373-mr-2017-0944
|View full text |Cite
|
Sign up to set email alerts
|

The Wire Drawing Mechanics of Near-Equiatomic NiTi SMA

Abstract: The wire drawing mechanic of Ti-49.82Ni (at. %) Shape Memory Alloy (SMA) was investigated through the true stress-strain curves and drawing stresses. The tensile tested solution treated wire presented a four steps elongation at temperatures below the austenite finish temperature (A F), and a conventional one-step behavior above the martensite deformation temperature (M D). The tensile yield stress for the formation of detwinned martensite (DTM) or stress-induced martensite (SIM) increased as the testing temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The inhomogeneous additional work component is closely related with the die geometry, diminishing when the approach angle is lower. For a low area reduction, most of the energy is spent as friction work, and the redundant work is relatively low 1 Geometric variables and the main zones in the wiredrawing process when 2 < ∆ < 3 [3]. Under normal conditions, friction effect constitutes nearly 20% of loses while 12% is due to the additional-redundant work.…”
Section: The Role Of Friction In the Wiredrawing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhomogeneous additional work component is closely related with the die geometry, diminishing when the approach angle is lower. For a low area reduction, most of the energy is spent as friction work, and the redundant work is relatively low 1 Geometric variables and the main zones in the wiredrawing process when 2 < ∆ < 3 [3]. Under normal conditions, friction effect constitutes nearly 20% of loses while 12% is due to the additional-redundant work.…”
Section: The Role Of Friction In the Wiredrawing Processmentioning
confidence: 99%
“…Many previous works consulted demonstrated the great importance of knowing reliably the value of the friction coefficient µ to be able to study analytically or numerically the wiredrawing process. It is so that, by the use of numerical models and methods, Chen and Huang [3] and Majzoobi et al [4] determined that 2β, Hc and the temperature profile into the die have a significant effect on the drawing process, but it is very important to consider the effect of the wire-die contact length (l) which determines the contact surface at the interface and has a direct effect on the lubrication conditions and, as a consequence, on the value of the friction coefficient µ, involved in the process. Another consulted works demonstrated the feasibility of the use of FEM applied to model the wiredrawing process and focused on the improvement of the geometry of the die [13], on the analysis of the strain distribution in the wire during the process [14] or even to analyze the distribution of residual stresses accumulated in the product once it has been shaped [15], among other output variables.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing is successfully used for the efficient processing of metallic biomaterials based on zinc [ 23 , 24 ], magnesium [ 25 ], titanium [ 26 , 27 ], and titanium nickelide [ 18 , 28 , 29 , 30 ]. It has been shown that CD of biodegradable Zn- and Mg-based alloys yields control of grain refinement, phase composition, and crystallographic texture to improve strength properties and corrosion behavior [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-temperature deformation, which makes it possible to carry out multi-pass drawings, seems to be more preferable for processing Ti-6Al-4V alloys and promotes grain refinement due to dynamic recrystallization and a corresponding increase in the strength of the alloy [ 31 ]. Multi-pass cold drawing, combined with thermal treatment, is effectively used to manufacture thin Ni-Ti wires for vascular stapling and orthodontics [ 28 , 29 ]. The nanocrystalline state with precipitation of dispersed Ti 3 Ni 4 particles, provided by controlled PDA after CD, makes it possible to achieve abnormally high recovery strains in the thin Ni-Ti wire [ 32 ].…”
Section: Introductionmentioning
confidence: 99%